Pergeseran dan Pemertahanan Kosa Kata Ngoko Krama Isolek Bahasa Jawa - Sugeng Triyanto; Ricky Perdana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purposes of this research are to explain the shifts on the language style from ngoko (N) to krama (K) and vice versa, from the Javanese isolect to other languages included their motivation, and to explain the Javanese language maintenance. This research is qualitative descriptive which the primary data are collected especially by using the direct observation method to the field of research as the practices of sociologists and anthropologists. The results of this research show that the shifts are closely related with status, intimateness, feeling, and activity. The maintenance is closely related with traditional life such as social value.